2002
DOI: 10.1046/j.1365-2222.2002.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Human mast cells stimulate fibroblast proliferation, collagen synthesis and lattice contraction: a direct role for mast cells in skin fibrosis

Abstract: We have shown that human mast cells, by granule-stored and therefore quickly releasable mediators, increase human skin fibroblast proliferation, collagen synthesis, TIMP-2 and collagen gel contraction. Therefore, mast cells have a direct and potentiating role in skin remodelling and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
121
1
11

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 42 publications
11
121
1
11
Order By: Relevance
“…26 Mast cells clearly play a role in regulating extracellular matrix metabolism during injury repair. Mast cell extracts have previously been shown in vitro to stimulate the production of collagen by skin fibroblasts, 27 and they are also capable of activating MMP activity, for instance via tryptase-mediated cleavage of MMP3. 28 An altered balance of collagen synthesis and secretion in response to mast cell activity would clearly affect the quantity and organizational properties of repair tissue.…”
Section: Mast Cells In Patellar Tendon Injurymentioning
confidence: 99%
“…26 Mast cells clearly play a role in regulating extracellular matrix metabolism during injury repair. Mast cell extracts have previously been shown in vitro to stimulate the production of collagen by skin fibroblasts, 27 and they are also capable of activating MMP activity, for instance via tryptase-mediated cleavage of MMP3. 28 An altered balance of collagen synthesis and secretion in response to mast cell activity would clearly affect the quantity and organizational properties of repair tissue.…”
Section: Mast Cells In Patellar Tendon Injurymentioning
confidence: 99%
“…The potential of mast cells to play a role in chronic asthma and airway remodeling is suggested from studies demonstrating an important role for mast cells in tissue fibrosis, including pulmonary fibrosis (10,11). Several mast cell-derived mediators are candidates for playing a role in mediating airway remodeling based on their demonstrated ability in vitro to influence fibroblast proliferation or collagen synthesis (12)(13)(14). For example, both histamine and tryptase stimulate fibroblast proliferation as well as collagen synthesis (12)(13)(14).…”
mentioning
confidence: 99%
“…Several mast cell-derived mediators are candidates for playing a role in mediating airway remodeling based on their demonstrated ability in vitro to influence fibroblast proliferation or collagen synthesis (12)(13)(14). For example, both histamine and tryptase stimulate fibroblast proliferation as well as collagen synthesis (12)(13)(14). In addition TGF-␤, a key cytokine-regulating fibrosis, is also generated by mast cells (15).…”
mentioning
confidence: 99%
“…[29,30] Mast cells have been associated with secretion of a number of important mediators of fibrosis. [31,32] It was shown that mast cells were present in higher numbers in inflammatory fibrous hyperplasia, as they were responsible for the adaptive and pathological responses in areas on chronic inflammation. [33] This was attributed due to the presence of a number of chemical mediators including histamines, proteases, chymase and tryptase within the secretory granules of the mast cells.…”
Section: Hande X 100mentioning
confidence: 99%